Variações em índices de área foliar e nos componentes do rendimento de grãos associadas com o uso de fungicidas em soja - Bortolin, Janaíne Lacourt de Souza (2020)
The soybean yield is influenced by the duration of the leaf area, so that the control of leaf diseases depends on the fungicide application phenological stage. The objective of this work was to evaluate the effect of chemical control with triazole and strobirulins, on the leaf area and yield components of cultivars from different maturity groups: semi-early (BRS 137), medium (BRS 154) and late (CD 205). The experiments were conducted in the field, in Passo Fundo, Rio Grande do Sul, Brazil, in the 2004-05. The treatment design was a bifactorial 5 (fungicide application stage) x 4 (fungicide) + 3 (without fungicide; two chemical treatment standards: SA and SB), arranged in randomized blocks with four replications. The following fungicides were applied, in a single dose, at stages R1, R2, R3, R4 or R5.1: a) tetraconazole (Domark®), b) epoxiconazole + piraclostrobin (Opera®), c) cyproconazole + azoxystrobin (Priori Xtra®) and d) cyproconazole + trifloxystrobin (Sphere®). The doses were according to the manufacturer's recommendation and in a volume of 150 L/ha. The standards constituted three applications, in stages R1, R3 and R5.1: SA) tetraconazole (triazole); SB) triazole + strobirulin: epoxiconazole + pyraclostrobin (R1), cyproconazole + azoxystrobin (R3) and cyproconazole + trifloxystrobin (R3). Assessments of disease severity, index (LAI) and duration (LAD) of leaf area and yield components were carried out. The cycle length of cultivars was 125 (BRS 137), 132 (BRS 154) and 145 days (CD 205). There was severe drought in the summer, which prevented the occurrence of leaf diseases at the end of the cycle; there was an incidence of powdery mildew (Microsphaera diffusa), with a maximum severity of 24%, but chemical control was greater than 80%. Standard treatments and mixtures of triazole + strobirulin did not differ (p> 0.05) in terms of response variables, but the fungicide application stage had a significant effect on LAD and yield components: a) single applications of triazole + strobirulin in stages R2 or R3 increased LAD and the thousand grain mass (TGM), in relation to those performed in R1, R4 or R5.1, but were similar to standard treatment; b) single application of triazole + strobirulin had a similar effect to standard treatment in the number of pods/plant, except if applied at the R1 stage, when this variable was reduced; c) single application of triazole + strobirulin had a similar effect to the standard treatment on the number of grains/pod, except if applied at the R5.1 stage, when it had a negative effect. The application of fungicides in R2 increased the LAI and LAD, which was reflected in the increase in TGM and grain yield. Grain yield was positively associated with TGM, but it was not related to the number of pods/plant and the number of grains/pod. In conclusion, the application of the fungicides at the R2 stage (full bloom) promotes a longer duration of the leaf area and, thus, increases the individual grain mass and the soybean productivity. The study shows that as the crop cycle decreases, the dependence on the duration of the leaf area increases, which makes preventive control of leaf diseases at the end of the cycle extremely relevant